Tellurium Doping Inducing Defect Passivation for Highly Effective Antimony Selenide Thin Film Solar Cell - Guojie Chen; Xiangye Li; Muhammad Abbas; Chen Fu; Zhenghua Su; Rong Tang; Shuo Chen; Ping Fan; Guangxing Liang (Nanomaterials)
Antimony selenide (Sb2Se3) is emerging as a promising photovoltaic material owing to its excellent photoelectric property. However, the low carrier transport efficiency, and detrimental surface oxidation of the Sb2Se3 thin film greatly influenced the further improvement of the device efficiency. In this study, the introduction of tellurium (Te) can induce the benign growth orientation and the desirable Sb/Se atomic ratio in the Te-Sb2Se3 thin film. Under various characterizations, it found that the Te-doping tended to form Sb2Te3-doped Sb2Se3, instead of alloy-type Sb2(Se,Te)3. After Te doping, the mitigation of surface oxidation has been confirmed by the Raman spectra. High-quality Te-Sb2Se3 thin films with preferred [hk1] orientation, large grain size, and low defect density can be successfully prepared. Consequently, a 7.61% efficiency Sb2Se3 solar cell has been achieved with a VOC of 474 mV, a JSC of 25.88 mA/cm2, and an FF of 64.09%. This work can provide an effective strategy for optimizing the physical properties of the Sb2Se3 absorber, and therefore the further efficiency improvement of the Sb2Se3 solar cells.